Ice flow line maps of three large freshwater calving glaciers in the Southern Patagonian Icefield - E. Lannutti; E. Lannutti; E. Lannutti; P. Marmolejo; J. Sanchez; I. Ortíz; M. G. Lenzano; S. Moragues; S. Moragues; A. Rivera; P. Vacaflor; G. Pereyra; et al. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The Southern Patagonian Icefield is experiencing rapid retreat and thinning in its calving glaciers. To better understand the dynamics of these changes, we generated ice flow line maps for the Viedma, Upsala, and Pio XI glaciers during 2017–2018. An evenly spaced streamline placement algorithm, integrating topographic and flow curvature criteria, was employed to calculate over 2,700 streamlines per glacier at a 50-meter resolution. The algorithm's performance was assessed by comparing the generated flow lines with manually digitized reference lines, resulting in a mean error, standard deviation, and root mean square error of 57.35, 33.62, and 66.46 meters, respectively. The resulting maps reveal detailed flow structures, highlighting flow lines from accumulation to ablation zones, increased velocities in central areas, tributary flows merging with main channels, and regions of flow convergence and divergence. Additionally, the glaciers' 3D lengths were estimated by identifying the longest ice flow lines, with Pio XI measuring 62.27 km, Viedma 54.49 km, and Upsala 51.24 km. We consider that the methodology used, along with the generated maps, provides excellent visual and analytical tools for identifying glacier areas, lengths, and shapes, defining ice origins and glacier catchment boundaries, and analysing zones of flow convergence and divergence—parameters that are critically important for understanding the dynamics, geometry, and evolution of glaciers in this region.